Ingrid Monson: Freedom Sounds. Civil Rights Call out to Jazz and Africa.: New York: Oxford University Press, 2007, 402 pp., photographs, music illustrations, appendices. - Reyes, Adelaida (Lidé města, 2010)
A review of the book by Ingrid Monson.